Active Disturbance Rejection Control for Robot Manipulator - Martínez-Ochoa, Carlos E.; Benítez-González, Ivón O.; Cepero-Díaz, Ariel O.; Nuñez-Alvarez, José R.; Miguélez-Machado, Carlos G.; Llosas-Albuerne, Yolanda E. (Universitas Muhammadiyah Yogyakarta, 2022)
Active Disturbance Rejection Control (ADRC) is a control methodology used in chemical processes, aircraft, motors, and other systems. This paper compares the results of an ADRC controller to a Proportional Integral Derivative controller (PID), applied to two degrees of freedom robots. A Linear Extended State Observer (LESO) is used to reconstruct the state variables and unknown parameters needed to control the position of each link. The ADRC can achieve the tracking position and estimate the velocity of each link. The results of the simulation program are shown.